En jämförelse av hopp- och dressyrhästens arbetsmängd med hjälp av applikationen Equilab - Gustafsson, Jenny; Larsson, Matilda (2020)
A comparison of workload between showjumpers and dressagehorses through the application Equilab. Horse owners and riders put a lot of time and effort how to train and feed the horse so it can perform as well as they want it to. How to feed the horse is easy to calculate and there are instructions for this that many use today. The problem is to estimate how to train the horse and how hard the horse is training. Studies have come to conclusions that how the horse is trained is the key to a long termed sustainable horse and that training is basically about strengthening the horse body to minimize the risk of injuries. The company Equilab has developed an application to track every ride. The application uses a GPS to track where you are riding, how fast, the distance, which gait, for how long and space to take notes after the training. In this study this application has been used to analyze and evaluate the workload of schoolhorses in both showjumping and dressage at the National Equestrian Centre Strömsholm. The questions are how does the everyday training and workload for showjumpers differ compared to dressage horses and how useful the Equilab application is to evaluate the workload of horses? It was 13 horses participating in the study and all of them were schoolhorses. Five of them were showjumpers and eight of them were dressagehorses. The rider of the horse wrote a note after every ride what type of training, the distance, time for every gait and the horses power consumption. The study went on for about four weeks. The feeding rations of the horses were registered, and the individual amount of daily energy intake was calculated. The result showed that showjumpers had significantly higher workload than dressagehorses. The result also showed that the feed energy intake for each horse were very similar to their needs. The conclusion was that there is a difference in the everyday work for showjumpers and dressagehorses. The difference was that the showjumpers gets a more varied schedule with a variation in types of work and a higher workload than the dressagehorses. The application Equilab was useful for forming an idea of how the horse is trained. However, a development of GPS receivers as well as the applications measurement of energy consumption is required to get a greater picture of the training.